The Value of PET/CT in Detecting Bone Marrow Involvement in Patients With Follicular Lymphoma - Perry, Chava (Medicine (Baltimore), 2016)
Follicular lymphoma (FL) is the 2nd most common type of lymphoma diagnosed in the Western World. Bone marrow (BM) involvement is an adverse prognostic factor in FL, routinely assessed by an arbitrary biopsy of the iliac crest. This study was aimed to investigate the role of positron emission tomography/computed tomography (PET/CT) in identifying BM involvement by FL. In this retrospective, single-center study we reviewed the records of consecutive patients with FL at diagnosis or relapse who underwent staging/restaging workup visual assessment of BM uptake was categorized as either normal, diffusely increased, or focally increased. Quantitative BM fluorine-18-fluro-deoxyglucose (FDG) uptake was measured using mean standardized uptake value (BM-SUV(mean)). The diagnosis of BM involvement was based on either BM histological findings or disappearance of increased uptake at end-treatment PET/CT in patients who responded to treatment. Sixty eight cases with FL were included. Sixteen (23.5%) had BM involvement, 13 (19.1%) had a biopsy proven involvement, and 3 (4.4%) had a negative BM biopsy, but increased medullary uptake that normalized post-treatment. BM FDG uptake in these patients was diffuse in 8 (50%) and focal in 8 (50%). Focal increased uptake was indicative of BM involvement; however, diffuse uptake was associated with 17 false positive cases (32.7%). Overall, visual assessment of BM involvement had a negative predictive value (NPV) of 100% and a positive predictive value (PPV) of 48.5%. On a quantitative assessment, BM-SUV(mean) was significantly higher in patients with BM involvement (SUV(mean) of 3.7 [1.7–6] vs 1.4 [0.4–2.65], P < 0.001). On receiver operator curve (ROC) analysis, BM-SUV(mean) > 2.7 had a PPV of 100% for BM involvement (sensitivity of 68%), while BM-SUV(mean) < 1.7 had an NPV of 100% (specificity of 73%). Visual assessment of PET/CT is appropriate for ruling out BM involvement by FL. Although focal increased uptake indicates marrow involvement, diffuse uptake is nonspecific. SUV measurement improves PET/CT diagnostic accuracy, identifying additional 19% of patients with BM involvement that would have been otherwise missed.